2005
DOI: 10.1002/elan.200403154
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Mechanism of Zn(II) Ions Electroreduction Catalyzed by Organic Compounds

Abstract: The paper describes the results of the studies of organic substances catalytic activity on Zn(II) ions electroreduction on mercury in perchlorate solutions. Zn(II) ions electroreduction in the presence of catalyzing substance proceeds in two one-electron stages. The first electron transfer is the stage determining the process rate. All catalyzing substances increase the rate of first electron transfer. The acceleration effect is connected with the stability of active complexes formed on the electrode surface. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 19 publications
1
25
0
Order By: Relevance
“…Probably the magnitude of the catalytic effect is connected to the equilibrium of reaction of active complexes formation before the transfer of consecutive electrons. A similar effect was observed by Dalmata [61] in his study on the catalytic activity of organic substances on the electroreduction process of Zn(II).…”
Section: Discussionsupporting
confidence: 83%
“…Probably the magnitude of the catalytic effect is connected to the equilibrium of reaction of active complexes formation before the transfer of consecutive electrons. A similar effect was observed by Dalmata [61] in his study on the catalytic activity of organic substances on the electroreduction process of Zn(II).…”
Section: Discussionsupporting
confidence: 83%
“…Studies on the kinetics of various depolarisers in the presence of electrode substances are comprehensively discussed in the literature [5][6][7][8][9][10][11]. It was demonstrated that the structures of the inter-phase area caused by adsorption of organic compounds on the surface of mercury play a significant role in the mechanism of the cap-pair effect.…”
Section: Introductionmentioning
confidence: 99%
“…The presented results allow for the following conclusions: -cystine, in accordance with cap -pair rule (Sykut 1978) (Dalmata 2005), accelerates the electroreduction of Bi(III) ions in chlorates (VII) solutions -the reversibility of Bi(III) ions electroreduction in chlorates (VII) depends on the cystine concentration and water activity -the optimal concentration of cystine and water activity for Bi(III) determination by voltammetric method were established. The presented method is fast, simple, relatively inexpensive and with easily accessible measurement system.…”
Section: Resultsmentioning
confidence: 57%
“…In agreement with cap -pair effect (Sykut 1978) (Dalmata 2005) the organic substances introduced to the supporting electrolyte can catalyze one type of electrode processes and simultaneously have no influence or even inhibit the other electrode processes. Such behaviour enables the determination of different elements near each other without necessity of analyte accumulation, what considerably simplifies the analysis procedure.…”
Section: Introductionmentioning
confidence: 67%